2023
DOI: 10.1093/cercor/bhac515
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into axon diameter and myelin content in late childhood and adolescence

Abstract: White matter microstructural development in late childhood and adolescence is driven predominantly by increasing axon density and myelin thickness. Ex vivo studies suggest that the increase in axon diameter drives developmental increases in axon density observed with pubertal onset. In this cross-sectional study, 50 typically developing participants aged 8–18 years were scanned using an ultra-strong gradient magnetic resonance imaging scanner. Microstructural properties, including apparent axon diameter $({d}_… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 107 publications
1
7
0
Order By: Relevance
“…Individuals with ASD also had significantly thinner myelin sheaths in all sizes of axon 50 . Though this histological experiment was performed in adults instead of the adolescents in this study, given these two factors, a bias toward smaller diameter axons and thinner myelin, it is likely that the results reported here confirm this prior finding, as the aggregate g-ratio in this adolescent cohort is overall lower than expected in adults due to insufficiently developed myelin, and thus the TD group can be interpreted as nearer to developed myelin and thus higher g- ratio closer to optimum values 52,84,94,95 . It has also been reported that children with ASD have lower conduction velocity using magnetoencephalography 96,97 and in peripheral neurons 98 , potentially due to reduced axonal diameter and the prevalence of small fibers.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Individuals with ASD also had significantly thinner myelin sheaths in all sizes of axon 50 . Though this histological experiment was performed in adults instead of the adolescents in this study, given these two factors, a bias toward smaller diameter axons and thinner myelin, it is likely that the results reported here confirm this prior finding, as the aggregate g-ratio in this adolescent cohort is overall lower than expected in adults due to insufficiently developed myelin, and thus the TD group can be interpreted as nearer to developed myelin and thus higher g- ratio closer to optimum values 52,84,94,95 . It has also been reported that children with ASD have lower conduction velocity using magnetoencephalography 96,97 and in peripheral neurons 98 , potentially due to reduced axonal diameter and the prevalence of small fibers.…”
Section: Discussionsupporting
confidence: 79%
“…12, the aggregate g-ratio can be lowered if both AVF and MVF are reduced, especially unequally. In absolute terms, it is possible that this adolescent cohort is overall lower than expected in adults due to insufficiently developed myelin and smaller axonal diameters, and thus the TD group can be interpreted as nearer to developed myelin/axonal volumes and thus the initially paradoxical seeming greater g-ratio compared to the ASD group is actually the result of higher axonal diameter[52,81,83,94]. Further comparison of these metrics to age shows that aggregate g-ratio has a negative relationship with age while aggregate conduction velocity has a positive relationship with age during this developmental period (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As illustrated in Fig 12 , the aggregate g-ratio can be lowered if both AVF and MVF are reduced, especially unequally. In absolute terms, it is possible that this adolescent cohort is overall lower than expected in adults due to insufficiently developed myelin and smaller axonal diameters, and thus the TD group can be interpreted as nearer to developed myelin/axonal volumes and thus the initially paradoxical seeming higher g-ratio compared to the ASD group is actually closer to optimum values [ 52 , 81 , 83 , 103 ]. It has also been reported that children with ASD have lower conduction velocity using magnetoencephalography [ 104 , 105 ] and in peripheral neurons [ 106 ], potentially due to reduced axonal diameter and the prevalence of small fibers.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, correlation between white matter changes and cognitive function over the course of human life establishes a link between myelin development and cognitive development. Longitudinal brain imaging studies have shown that white matter volume—reflecting the myelin content and axonal caliber [ 81 ]—has a linear increase throughout childhood and adolescence ([ 82 ] reviews such findings while discussing various myelin imaging techniques and their shortcomings). As first reported by fractional anisotropy, a measure of white matter volume in diffusion tensor imaging (DTI), an increase of myelin thickness in frontal white matter positively correlates with increased working memory scope in children [ 83 ].…”
Section: Myelin In Cognitive Processingmentioning
confidence: 99%